Character Education in the Digital Era for Elementary School Students - Suryani, Suryani (PPSDP International Journal of Education, 2024)
Character building is the process of applying manners and religion to students through knowing and applying these values to themselves, their families, all their friends, their teachers, their environment, and the Almighty God. The social development of elementary school students is progressing. From the beginning, he played alone with his family at home, and then he met other people in his environment. Children this age are familiar with the digital style at home, with friends, at school, and in the community. The digital age has both negative and positive impacts. In this case, parents, teachers, and the community try to guide and observe the children to be good, excel, and set positive goals.